Deindividuation in the online social networking context : What situations might encourage deindividuation on Facebook? : a research proposal [sic] presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany campus, New Zealand - Birch, Emily Sarah (Massey University, 2010)
Deindividuation occurs when group members perceive they no longer stand out as individuals, and their perceived anonymity enables engagement in behavior they would normally refrain from performing. The study utilized a 2x2 between-subjects experimental design to assess the impact of visual anonymity (low versus high) and salient social identity (group versus individual) on willingness to admit to holding socially undesirable views on a purpose-built Facebook profile page. Participants were requested to (1) follow administrative instructions and view a within-Facebook Group Webpage, (2) anonymously respond to controversial statements, (3) complete the Balanced Inventory of Desirable Responding, and (4) reiterate their responses to the statements on a Facebook group page. Participants assigned to the high visual anonymity condition were asked to use the default Facebook profile image as their profile picture, while those in the low visual anonymity condition were requested to upload a portrait-style photograph. The salient social identity (individual or group) was manipulated by referring to participants as either “individuals” or “group members”, assigning either a “participant number” or a “group member number”, and explaining the purpose of the study as an investigation of the effect of social processes on either “individual” or “group members”. As predicted by the Social Identity model of Deindividuation Effects (SIDE model), visual anonymity and salient social identity were found to elicit an interaction effect on the degree to which numerical responses to the statement “fat people are lazy” was influenced by deindividuation, when the statement was presented on a Facebook group page. This finding was validated by the lack of significant differences between numerical responses to the statements on the anonymous survey website, and consistent scores on the Balanced Inventory of Desirable Responding between experimental groups. However, the three of the other controversial statements did not result in significant differences on Facebook, and the remaining controversial statement did not elicit significant responses in the predicted direction. Possible explanations for this finding are discussed, and recommendations for future research are presented.
Keywords: Online social networks; Online behavior; Online identity; Facebook; Social identity